Synthesis of bendable plasticized nanocomposite polymer electrolyte using poly(acrylonitrile) poly(methyl methacrylate) polymer blends - Flora, Xavier Helan (2015)
A class of nanocomposite polymer electrolytes (NCPE) with high ionic conductivity was prepared by blending of poly(acrylonitrile) and poly(methyl methacrylate) polymers. Lithium bis(trifluoromethanesulfonimide) (LiN(CF3SO2)2), Ethylene carbonate (EC), Barium titanate (BaTiO3) was used as ionic salt, plasticizers and ceramic filler, respectively. Role of inorganic ceramic filler on structural and ionic conductivity of the polymer electrolyte was investigated for various concentrations of BaTiO3 filler. The structural elucidation, complex formation of the prepared electrolytes is ascertained from XRD, FTIR analysis. All the samples were subjected to complex ac impedance analysis for obtaining the bulk resistance of the composite electrolytes. It was found that the sample containing 10 wt. % of filler showed maximum ionic conductivity than the other samples. Thermal stability and surface morphology of the composite polymer electrolytes were also examined by thermogravimetric analysis and scanning electron microscope, respectively.